2022
DOI: 10.3389/fphar.2022.873023
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Experimental Verification Strategies to Illustrate the Mechanism of Jian-Pi-Yi-Shen Formula in Suppressing Epithelial–Mesenchymal Transition

Abstract: Jian-Pi-Yi-Shen formula (JPYSF), a traditional Chinese medicine, has been recommended to treat renal fibrosis for decades. Previous studies had shown that JPYSF could inhibit epithelial–mesenchymal transition (EMT), an important regulatory role in renal fibrosis. However, the mechanism of JPYSF action is largely unknown. In this study, network pharmacology and experimental verification were combined to elucidate and identify the potential mechanism of JPYSF against renal fibrosis by suppressing EMT at molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Studies have shown that JPYSF protected kidney from fibrotic injury [12,13,51]. Some active ingredients in JPYSF have been reported to exert anti-fibrotic effects through acting on cellular signal pathways, such as inhibiting the TGF-β1 pathway, activating Sirt1-mediated autophagy, and inhibiting the Wnt3a/β-catenin pathway [52][53][54][55][56]. Our data suggested that JPYSF alleviates renal fibrosis by restoring NAD + biosynthesis.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have shown that JPYSF protected kidney from fibrotic injury [12,13,51]. Some active ingredients in JPYSF have been reported to exert anti-fibrotic effects through acting on cellular signal pathways, such as inhibiting the TGF-β1 pathway, activating Sirt1-mediated autophagy, and inhibiting the Wnt3a/β-catenin pathway [52][53][54][55][56]. Our data suggested that JPYSF alleviates renal fibrosis by restoring NAD + biosynthesis.…”
Section: Discussionmentioning
confidence: 55%
“…It has been shown that single herbs (Liu et al, 2022;Qian et al, 2022), herbal extracts (Yu, 2020;Zheng et al, 2021;Cong et al, 2022;Ma et al, 2022), and Chinese medicine compounds (Chen et al, 2022a;Chen et al, 2022b;Wu et al, 2022;Zhao et al, 2022) have made great progress in the prevention and even treatment of renal fibrosis (Xu et al, 2021). They regulate multiple signaling pathways such as Wnt/β-catenin (Zhao et al, 2022), TGF-β1/Smad (Mao et al, 2019;Wu et al, 2022), Akt/mTOR (Lian et al, 2022), CX3CL1-RAF/MEK/ ERK (Hu et al, 2022b), mTORC1/p70S6K (Chen et al, 2019), SIRT1-NF-κB (Wang et al, 2018b), and interfere with different cytokine or inflammatory factors expression to regulate the development and progression of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that single herbs (Liu et al, 2022;Qian et al, 2022), herbal extracts (Yu, 2020;Zheng et al, 2021;Cong et al, 2022;Ma et al, 2022), and Chinese medicine compounds (Chen et al, 2022a;Chen et al, 2022b;Wu et al, 2022;Zhao et al, 2022) have made great progress in the prevention and even treatment of renal fibrosis (Xu et al, 2021). They regulate multiple signaling pathways such as Wnt/β-catenin (Zhao et al, 2022), TGF-β1/Smad (Mao et al, 2019;Wu et al, 2022), Akt/mTOR (Lian et al, 2022), CX3CL1-RAF/MEK/ ERK (Hu et al, 2022b), mTORC1/p70S6K (Chen et al, 2019), SIRT1-NF-κB (Wang et al, 2018b), and interfere with different cytokine or inflammatory factors expression to regulate the development and progression of renal fibrosis. The Chinese herbal extract AS-IV, which has been widely recognized to have significant anti-nephrogenic effects (Yu, 2020;Fu et al, 2022), is the main active component of Huangqi, a Chinese herbal medicine, and its mechanism has been richly studied and Frontiers in Pharmacology frontiersin.org repeatedly validated (Wang et al, 2018b;Chen et al, 2019;Mao et al, 2019;Hu et al, 2022b;Lian et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org (50 mg/kg) after intraperitoneal injection (Zhao et al, 2022). Five milliliters of abdominal aortic blood were collected and placed into the test tube, centrifuged at 3,000 r/min at 4 °C for 15 min, and the separated supernatant was placed into the refrigerator at −80 °C for testing.…”
Section: Experimentals Animals and Modelingmentioning
confidence: 99%